VISUAL NOVEL GAME BIMA’S ADVENTURE: DEVELOPMENT OF LEARNING MEDIA ON THE TOPIC OF EARTH ATMOSPHERIC LAYERS IN ELEMENTARY SCHOOL - Salsabilla, Zahra; Suryanti; Julianto; Istianah, Farida (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
Several concepts in science subjects are abstract, making it difficult for students to understand the material and resulting in low learning outcomes. This issue is further exacerbated by the limited use of engaging learning media that support deep conceptual understanding. To address this issue, a visual novel-based learning media titled